2013
DOI: 10.1149/2.114311jes
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Chemical Stabilities and Electrical Conductivity of Fe-Doped Manganese Cobalt Spinel Oxides for SOFC Interconnect Coatings

Abstract: The application of ceramic coatings has been demonstrated as an effective technique to suppress the oxidation scale growth and chromium volatilization of ferritic stainless steels used for SOFC interconnects. Manganese cobalt spinel oxides are promising materials for this application. In this work, the effects of iron doping in the MnCo2-xFexO4 (x = 0–0.7) spinel oxide on the crystal structure, reaction with chromia, cation distributions, and electrical conductivity at high temperature were investigated. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…For example, [49] reported 34 S/cm at 800 °C in air for a sample sintered at 1200 °C and [78] reported 40 S/cm for a sample sintered at 1300 °C. As previously discussed by Liu et al [48] some of the discrepancies found in literature are most likely due to the high temperature at which many of the investigated samples have been sintered. According to the Mn3O4-Co3O4 phase diagram reported by Aukrust and Muan [65], the MnCo2O4 spinel is only stable up to ca.…”
Section: Electrical Conductivitymentioning
confidence: 87%
See 3 more Smart Citations
“…For example, [49] reported 34 S/cm at 800 °C in air for a sample sintered at 1200 °C and [78] reported 40 S/cm for a sample sintered at 1300 °C. As previously discussed by Liu et al [48] some of the discrepancies found in literature are most likely due to the high temperature at which many of the investigated samples have been sintered. According to the Mn3O4-Co3O4 phase diagram reported by Aukrust and Muan [65], the MnCo2O4 spinel is only stable up to ca.…”
Section: Electrical Conductivitymentioning
confidence: 87%
“…Previous investigations of the cation distribution in MnCo2-xFexO4 have suggested both a mixed occupancy of Fe on tetrahedral and octahedral sites [48], and that Fe mainly occupies the latter [73]. Crystal field theory predicts that both Mn 3+ and Co 3+ have a stronger preference for the octahedral site than Fe 3+ [74].…”
Section: Crystal Structurementioning
confidence: 94%
See 2 more Smart Citations
“…Both materials have appreciable electrical conductivity (60-90 S cm -1 at 800 °C [11,12]) and an acceptable thermal expansion coefficient (TEC) (11.4-14.4×10 -6 K -1 between 25 °C and 800 °C [13][14][15]). Attempts to improve the (Mn,Co) 3 O 4 coating material by substituting some of the Co with Fe or Cu have been reported [13,[16][17][18][19][20][21]. The TEC of MnCo 2 O 4 is reduced by replacing some of the Co with Fe, which in some cases may be advantageous depending on what type of cell the interconnect is connected to [15].…”
Section: Introductionmentioning
confidence: 99%